Method for preparing all-solid waste cement product by utilizing mineralization of cement kiln tail flue gas
Through the mineralization of the flue gas at the cement kiln tail, a high-strength carbon-cured magnesium slag block is formed, which solves the problems of magnesium slag recycling and carbon emissions, and achieves the sustainable development and environmental protection goals of building materials.
Patent Information
- Application Number
- CN202411483939.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-07
AI Technical Summary
The existing technology is difficult to effectively recycle magnesium slag, and carbon dioxide flue gas emissions and open-pit storage of magnesium slag during magnesium refining have negative impacts on the environment. There is a lack of high-value and high-utility magnesium slag recycling methods, which affects the sustainability of building materials. develop.
The method of preparing all-solid waste cement products by mineralizing the flue gas at the tail of cement kiln is used to collect magnesium slag powder and water to form a slurry, and the mineralization is used to control the temperature and time to form a high-strength and environmental protection. carbon-cured magnesium slag blocks.
It has achieved efficient recycling and carbon capture of magnesium slag, reduced carbon dioxide emissions, reduced traditional cement usage, improved the strength and durability of building materials, has a wide range of application, low treatment cost, and is in line with the Sustainable Development Goals.
Smart Images

Figure CN119263664A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement preparation, and in particular to a method for preparing all-solid waste cement products by mineralizing cement kiln tail flue gas. Background Art
[0002] Pidgeon magnesium slag is a solid powder waste discharged during the industrial magnesium smelting process. Due to its high basicity and high content of heavy metals, Pidgeon magnesium slag is more difficult to recycle than other industrial solid wastes. In addition, a large amount of carbon dioxide flue gas is discharged into the atmosphere during the magnesium smelting process, and the open-air storage and treatment of magnesium slag has a huge negative impact on the ecological environment.
[0003] Therefore, current research needs to improve and design a method for recycling magnesium slag with high value and high utilization rate, and improve the quality control level of magnesium slag, reduce the use of cement and reduce carbon emissions, and further promote the sustainable development of the building materials industry. Summary of the invention
[0004] Technical issues solved:
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing all-solid waste cement products by mineralizing cement kiln tail gas, which has the advantages of simple operation, high efficiency, wide application range, low processing cost, and environmental friendliness, and solves the problems of the above-mentioned technologies.
[0006] Technical solution:
[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing all-solid waste cement products by mineralizing cement kiln tail gas, comprising the following steps:
[0008] Step 1: Preparation of magnesium slag: Collect magnesium slag produced during magnesium smelting by industrial Pijiang method / silicothermic reduction method, and grind it into fine powder;
[0009] Step 2, preparation of magnesium slag slurry: uniformly mixing the dried magnesium slag powder and water according to the target water-cement ratio to obtain a freshly mixed magnesium slag slurry;
[0010] Step 3: Forming: pouring the magnesium slag slurry into a mold, forming it by oscillation, and demoulding it after preliminary solidification to obtain a magnesium slag block;
[0011] Step 4: Mineralization treatment: Place the demoulded magnesium slag blocks in the mineralization box of the carbon capture device, inject CO2 gas into the mineralization box, and its volume concentration should be ≥30%; CO2 gas is introduced or purged through the inside or surface of the magnesium slag blocks to achieve mineralization;
[0012] Step 5: Mineralization condition control: control the temperature of mineralization treatment to ≥ 0°C and the duration of mineralization treatment to ≥ 60 minutes;
[0013] Step 6. Static curing: Before demoulding the prepared magnesium slag blocks, place them in a standard curing room for 24 hours.
[0014] Preferably, in step 2, the mixing water accounts for 0.2-0.4 wt%, and the Pidgeon magnesium slag accounts for 100 wt%.
[0015] Preferably, the volume concentration of CO2 gas in step 4 is ≥40%.
[0016] Preferably, the mineralization treatment is adjusted according to the carbon mineralization demand of the magnesium slag building block, and the duration of the mineralization treatment is ≥120 minutes.
[0017] Preferably, the mold volume in step 3 is 40*40*160mm 3 .
[0018] Preferably, the content of silicon dioxide SiO2 in the Pidgeon process magnesium slag is 29.88wt%; the content of aluminum oxide Al2O3 in the Pidgeon process magnesium slag is 1.06wt%; and the content of CaO in the Pidgeon process magnesium slag is 50.98wt%.
[0019] Preferably, the CO2 gas captured by cooling is waste gas containing CO2 generated during fuel combustion and production process in a cement plant.
[0020] Preferably, the Pijiang magnesium slag in step 1 comprises the following components: silicon dioxide SiO2, aluminum oxide Al2O3, calcium oxide CaO, iron oxide Fe2O 3 , magnesium oxide MgO.
[0021] Preferably, the fineness of the Pidgeon magnesium slag in step 1 is less than 75 μm.
[0022] Preferably, the temperature for casting the magnesium slag blocks is 19-21°C.
[0023] Compared with the prior art, the present invention provides a method for preparing all-solid waste cement products by mineralizing cement kiln tail gas, which has the following beneficial effects:
[0024] 1. The present invention uses Pijiang magnesium slag as the main raw material. Magnesium slag is an industrial by-product produced in the steel production process. It is rich in resources and low in cost. It effectively reduces the complexity of raw material procurement. The fineness of magnesium slag powder is less than 75μm, which ensures the consistency and reliability of raw materials and reduces the variables in the later processing process. By controlling the proportion of water to 0.2-0.4wt%, the fluidity and formability of the slurry are optimized, which is convenient for subsequent casting and molding. A standardized mold of 40×40×160mm is used. 3 , simplifies the molding process, ensures consistent block size and shape, facilitates subsequent processing and transportation, sets the mineralization treatment time ≥ 60 minutes, preferably ≥ 120 minutes and the temperature ≥ 0°C, combined with an appropriate CO2 concentration of ≥ 40%, can achieve high-efficiency mineralization reaction in a relatively short time, improve the strength and stability of cement products, use the CO2 waste gas generated by the cement plant itself as a mineralization source, reduce the complexity of external gas procurement, and realize the recycling of resources, achieving the beneficial effects of simple operation and high efficiency.
[0025] 2. The present invention adjusts the water-cement ratio, mineralization temperature and time process parameters to adapt to the processing requirements of magnesium slag or other wastes of different properties, and is easy to apply in different industrial environments. The CO2 generated by the cement kiln is used as the mineralization source, which avoids the need to purchase external chemical reagents, complies with environmental protection policies and sustainable development goals, and makes the method easier to promote in many regions. Magnesium slag as a raw material is a by-product of steel production, and its cost is relatively low, which reduces the dependence on expensive raw materials and reduces the overall production cost from the raw material procurement cost. The CO2 in the cement kiln exhaust gas is used for mineralization, which significantly reduces the gas source that needs to be purchased externally, which not only reduces the production cost, but also makes the entire process more environmentally friendly, conforming to the trend of industrial low-carbon development. By optimizing the slurry ratio and standardizing the molding process, human errors and resource waste in the production process are reduced, and the production efficiency is further improved, thereby reducing the cost of manpower and equipment. The cement kiln exhaust gas and magnesium slag are processed into building materials products, achieving the beneficial effects of wide application range and low processing cost.
[0026] 3. The present invention avoids releasing the CO2 waste gas generated by the cement kiln into the environment, thereby effectively reducing the emission of carbon dioxide, helping to achieve carbon capture and utilization (CCU), and contributing to the reduction of greenhouse gases. The solid waste: magnesium slag is used for mineralization treatment, which effectively reduces the soil and water pollution that may be caused by traditional waste treatment. The waste gas is mineralized into building materials products, further reducing the burden on the environment. The traditional cement production process is usually accompanied by high carbon dioxide emissions. Through this method, the amount of traditional cement is reduced, and CO2 is used to reduce the overall carbon footprint. The mineralized magnesium slag material can be used to produce cement products with good mechanical properties and durability. Compared with traditional materials, it has a longer service life, thereby reducing the resource consumption and environmental impact caused by frequent maintenance and replacement. This method is in line with the global trend of rising demand for sustainable building materials, helps to build green buildings, and achieves beneficial effects that are environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the steps of the present invention;
[0028] Figure 2 This is a schematic diagram of the XRD of the Pidgeon process magnesium slag of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] See also Figure 1 A method for preparing all-solid waste cement products by mineralizing cement kiln tail gas, comprising the following steps:
[0031] Step 1: Preparation of magnesium slag: Collect magnesium slag produced during magnesium smelting by industrial Pijiang method / silicothermic reduction method, and grind it into fine powder;
[0032] Step 2, preparation of magnesium slag slurry: uniformly mixing the dried magnesium slag powder and water according to the target water-cement ratio to obtain a freshly mixed magnesium slag slurry;
[0033] Step 3: Forming: pouring the magnesium slag slurry into a mold, forming it by oscillation, and demoulding it after preliminary solidification to obtain a magnesium slag block;
[0034] Step 4: Mineralization treatment: Place the demoulded magnesium slag blocks in the mineralization box of the carbon capture device, inject CO2 gas into the mineralization box, and its volume concentration should be ≥30%; CO2 gas is introduced or purged through the inside or surface of the magnesium slag blocks to achieve mineralization;
[0035] Step 5: Mineralization condition control: control the temperature of mineralization treatment to ≥ 0°C and the duration of mineralization treatment to ≥ 60 minutes;
[0036] Step 6. Static curing: Before demoulding the prepared magnesium slag blocks, place them in a standard curing room for 24 hours.
[0037] The method mainly utilizes magnesium slag, which is a common industrial by-product with a wide range of sources. Other types of solid waste: fly ash and slag are also suitable for such mineralization treatment, which increases the flexibility and adaptability of the method.
[0038] Adjustability of process parameters: By adjusting process parameters such as water-cement ratio, mineralization temperature and time, this method can adapt to the processing needs of magnesium slag or other wastes of different properties, and is easy to apply in different industrial environments.
[0039] Environmental friendliness: Using CO2 produced by cement kilns as a mineralization source avoids the need to purchase external chemical reagents, complies with environmental protection policies and sustainable development goals, and makes this method easier to promote in many regions.
[0040] Utilization of industrial by-products: Magnesium slag as a raw material is a by-product of steel production, and its cost is relatively low, which reduces the dependence on expensive raw materials and reduces the overall production cost from the raw material procurement cost.
[0041] Recycling CO2: Using CO2 from cement kiln tail gas for mineralization significantly reduces the need to purchase gas from outside. This not only reduces production costs, but also makes the entire process more environmentally friendly, in line with the trend of industrial low-carbon development.
[0042] Simplify the process flow: By optimizing the slurry ratio and standardizing the molding process, human errors and resource waste in the production process are reduced, and production efficiency is further improved, thereby reducing the cost of manpower and equipment.
[0043] Reduce waste disposal costs: By treating cement kiln exhaust gas and magnesium slag into building materials, this method not only turns waste into treasure, but also reduces the cost of environmental governance, reflecting the dual advantages of economic and environmental benefits.
[0044] Specifically, in step 2, the mixing water accounts for 0.2-0.4 wt%, and the Pidgeon magnesium slag accounts for 100 wt%.
[0045] Specifically, in step 4, the volume concentration of CO2 gas is ≥40%.
[0046] Specifically, the mineralization treatment is adjusted according to the carbon mineralization demand of the magnesium slag blocks, and the duration of the mineralization treatment is ≥120 minutes.
[0047] Specifically, the mold volume in step 3 is 40*40*160mm 3 .
[0048] Specifically, the content of silicon dioxide SiO2 in the Pidgeon process magnesium slag is 29.88wt%; the content of aluminum oxide Al2O3 in the Pidgeon process magnesium slag is 1.06wt%; and the content of CaO in the Pidgeon process magnesium slag is 50.98wt%.
[0049] Specifically, the CO2 gas captured by cooling is the waste gas containing CO2 generated during the fuel combustion and production process in the cement plant.
[0050] Specifically, the Pijiang process magnesium slag in step 1 includes the following components: silicon dioxide SiO2, aluminum oxide Al2O3, calcium oxide CaO, iron oxide Fe2O 3 , magnesium oxide MgO.
[0051] Specifically, the fineness of the Pidgeon magnesium slag in step 1 is less than 75 μm.
[0052] Specifically, the temperature for casting the magnesium slag blocks is 19-21°C.
[0053] The carbon-cured building blocks in the present invention use Pidgeon magnesium slag as raw material, and are subjected to mineralization curing after being made into building blocks. Since the CO2 gas at the tail of the cement kiln is used for curing, the emission of polluting gases is reduced. In the cementitious material prepared by the preparation method, calcium / magnesium-based minerals such as C2S and hydration products (calcium hydroxide Ca(OH)2 and calcium silicate hydrate CSH) can participate in the carbonization reaction to form thermodynamically stable calcium carbonate and silica gel with volcanic ash activity, thereby improving the strength of the cementitious material and improving the internal pore structure, that is, excellent mechanical properties can be obtained through short-term carbonization curing.
[0054] The present invention provides a carbon-solidified magnesium slag building block, comprising the following minerals in mass percentage: C2S: 50-70% (e.g., 50%, 56%, 57%, 58%, 59%, 60%, 66%, 67%, 68%, 69%, 70%), MgO: 5-10% (e.g., 5%, 6%, 7%, 8%, 9%, 10%). C2S is dicalcium silicate, and MgO is magnesium oxide.
[0055] Preferably, the carbon-solidified magnesium slag building block comprises the following minerals in percentage by mass: C2S: 50-70% (e.g., 50%, 56%, 57%, 58%, 59%, 60%, 66%, 67%, 68%, 69%, 70%), MgO: 5-10% (e.g., 5%, 6%, 7%, 8%, 9%, 10%)
[0056] The products of mineral hydration such as calcium silicate in carbon-solidified magnesium slag blocks undergo carbonization reaction with CO2. The generated gel and calcium carbonate greatly improve the pore structure in the magnesium slag slurry, thereby forming a tight skeleton structure, making the magnesium slag blocks denser and improving their mechanical properties.
[0057] In a specific embodiment of the present invention, the Pidgeon process magnesium slag includes the following components: SiO2, Al2O3, Fe2O3, CaO and MgO.
[0058] The content of SiO2 in the Pijiang process magnesium slag is 25-30wt% (e.g., 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%);
[0059] In a specific embodiment of the present invention, the purpose of the oscillation molding in step 1 is to allow the mixed raw materials to fully contact each other and eliminate the pores caused by internal bubbles.
[0060] Step 2: Curing the magnesium slag blocks obtained in step 1 is to allow solid phase reaction to occur inside the magnesium slag blocks, and magnesium slag blocks are obtained after 24 hours.
[0061] In a specific embodiment of the present invention, the curing temperature in step 2 is 19-21° C. (for example, 19° C., 20° C., 21° C.), and the relative humidity is ≧90% (for example, 90%, 91%, 92%, 93%).
[0062] In the specific embodiment of the present invention, the carbonization capture device in step 3 is independently designed. The carbon dioxide concentration is 40-60% (for example, 40%, 50%, 60%). The carbon dioxide maintenance technology process is as follows Figure 1 As shown, 1 is the flue gas from the cement kiln; 2 is the carbon dioxide capture system (the concentration of the captured carbon dioxide flue gas is 40-65%, and the temperature is 25-30°C); 3 is the product mineralization curing room.
[0063] Among the raw materials used in the following examples and comparative examples, the Pijiang process magnesium slag was taken from Desheng Company in Leshan, Sichuan. The chemical composition of the raw materials is shown in Table 1 below.
[0064] Table 1 Chemical composition of magnesium slag
[0065]
[0066] like Figure 2 As shown in the figure, it is the XRD spectrum of the Pidgeon process magnesium slag used in the following embodiments and control examples. The XRD phase analysis results show that the phase of the Pidgeon process magnesium slag is mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0067] Example 1
[0068] The embodiment of the present invention provides a method for preparing a carbon-cured cement block, comprising the following steps:
[0069] Step 1: Mix water and Pidgeon magnesium slag evenly at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0070] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0071] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 6 hours. The volume concentration of the CO2 industrial tail gas is 40%, and the flow rate of the CO2 gas is 31.6Nm 3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry blocks.
[0072] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0073] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0074] Performance Testing
[0075] The compressive strength of the carbon-solidified magnesium slag slurry block prepared in the embodiment of the present invention after carbonization curing for 6 hours is 34.6 MPa, and the flexural strength is 5.6 MPa, as shown in Table 2.
[0076] Table 2 Mechanical properties after carbonization curing for 6 hours (MPa)
[0077]
[0078] Example 2
[0079] The embodiment of the present invention provides a method for preparing a carbon-solidified magnesium slag building block, comprising the following steps:
[0080] Step 1: Mix water and Pidgeon magnesium slag evenly at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0081] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0082] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 12 hours. The volume concentration of the CO2 industrial tail gas is 40%, and the flow rate of the CO2 gas is 31.6Nm 3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry blocks.
[0083] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0084] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0085] Performance Testing
[0086] The compressive strength of the carbon-solidified magnesium slag block prepared in the embodiment of the present invention after carbonization curing for 12 hours is 43.6 MPa, and the flexural strength is 5.7 MPa, as shown in Table 3.
[0087] Table 3 Mechanical properties after carbonization curing for 12 hours (MPa)
[0088]
[0089] Example 3
[0090] The embodiment of the present invention provides a method for preparing a carbon-cured cement block, comprising the following steps:
[0091] Step 1: Mix water and Pidgeon magnesium slag evenly at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0092] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0093] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 24 hours. The volume concentration of the CO2 industrial tail gas is 40%, and the flow rate of the CO2 gas is 31.6Nm3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry mortar blocks.
[0094] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0095] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0096] Performance Testing
[0097] The compressive strength of the carbon-solidified magnesium slag slurry block prepared in the embodiment of the present invention after carbonization curing for 24 hours is 50.5 MPa, and the flexural strength is 5.9 MPa, as shown in Table 4.
[0098] Table 4 Mechanical properties after carbonization curing for 24 hours (MPa)
[0099]
[0100] Example 4
[0101] The embodiment of the present invention provides a method for preparing a carbon-cured cement block, comprising the following steps:
[0102] Step 1: Mix water and Pidgeon magnesium slag evenly at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0103] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0104] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 72 hours. The volume concentration of the CO2 industrial tail gas is 40%, and the flow rate of the CO2 gas is 31.6Nm 3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry blocks.
[0105] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0106] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0107] Performance Testing
[0108] The compressive strength of the carbon-solidified magnesium slag block prepared in the embodiment of the present invention after carbonization curing for 72 hours is 54 MPa, and the flexural strength is 6 MPa, as shown in Table 5.
[0109] Table 5 Mechanical properties after carbonization curing for 72 hours (MPa)
[0110]
[0111] Example 5
[0112] The embodiment of the present invention provides a method for preparing a carbon-solidified magnesium slag building block, comprising the following steps:
[0113] Step 1: Mix water and Pidgeon magnesium slag evenly at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0114] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0115] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 6 hours. The volume concentration of the CO2 industrial tail gas is 50%, and the flow rate of the CO2 gas is 31.6Nm 3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry blocks.
[0116] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0117] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0118] Performance Testing
[0119] The compressive strength of the carbon-solidified magnesium slag block prepared in the embodiment of the present invention after carbonization curing for 6 hours is 34 MPa, and the flexural strength is 5.8 MPa, as shown in Table 6.
[0120] Table 6 Mechanical properties after carbonization curing for 6 hours (MPa)
[0121]
[0122]
[0123] Example 6
[0124] The embodiment of the present invention provides a method for preparing a carbon-solidified magnesium slag building block, comprising the following steps:
[0125] Step 1: Mix water and Pidgeon magnesium slag evenly at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0126] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0127] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 12 hours. The volume concentration of the CO2 industrial tail gas is 50%, and the flow rate of the CO2 gas is 31.6Nm 3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry blocks.
[0128] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0129] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0130] Performance Testing
[0131] The compressive strength of the carbon-solidified magnesium slag block prepared in the embodiment of the present invention after carbonization curing for 12 hours is 44.6 MPa, and the flexural strength is 5.9 MPa, as shown in Table 7.
[0132] Table 7 Mechanical properties after carbonization curing for 12 hours (MPa)
[0133]
[0134] Example 7
[0135] The embodiment of the present invention provides a method for preparing a carbon-solidified magnesium slag building block, comprising the following steps:
[0136] Step 1: Mix water and Pidgeon magnesium slag evenly at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0137] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0138] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 24 hours. The volume concentration of the CO2 industrial tail gas is 50%, and the flow rate of the CO2 gas is 31.6Nm 3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry blocks.
[0139] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0140] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0141] Performance Testing
[0142] The compressive strength of the carbon-solidified magnesium slag block prepared in the embodiment of the present invention after carbonization curing for 24 hours is 58 MPa, and the flexural strength is 6.0 MPa, as shown in Table 8.
[0143] Table 8 Mechanical properties after carbonization curing for 24 hours (MPa)
[0144]
[0145] Example 8
[0146] The embodiment of the present invention provides a method for preparing a carbon-solidified magnesium slag building block, comprising the following steps:
[0147] Step 1: Evenly mix water with Pidgeon magnesium slag at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0148] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0149] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 72 hours. The volume concentration of the CO2 industrial tail gas is 50%, and the flow rate of the CO2 gas is 31.6Nm 3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry blocks.
[0150] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0151] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0152] Performance Testing
[0153] The compressive strength of the carbon-solidified magnesium slag block prepared in the embodiment of the present invention after carbonization curing for 72 hours is 55.2 MPa, and the flexural strength is 6.1 MPa, as shown in Table 9.
[0154] Table 9 Mechanical properties after carbonization curing for 72 hours (MPa)
[0155]
[0156] Example 9
[0157] The embodiment of the present invention provides a method for preparing a carbon-solidified magnesium slag building block, comprising the following steps:
[0158] Step 1: Mix water and Pidgeon magnesium slag evenly at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0159] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0160] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 6 hours. The volume concentration of the CO2 industrial tail gas is 60%, and the flow rate of the CO2 gas is 31.6Nm 3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry blocks.
[0161] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0162] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0163] Performance Testing
[0164] The compressive strength of the carbon-solidified magnesium slag block prepared in the embodiment of the present invention after carbonization curing for 6 hours is 45.2 MPa, and the flexural strength is 5.7 MPa, as shown in Table 10.
[0165] Table 10 Mechanical properties after carbonization curing for 6 hours (MPa)
[0166]
[0167] Example 10
[0168] The embodiment of the present invention provides a method for preparing a carbon-solidified magnesium slag building block, comprising the following steps:
[0169] Step 1: Mix water and Pidgeon magnesium slag evenly at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0170] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0171] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 12 hours. The volume concentration of the CO2 industrial tail gas is 60%, and the flow rate of the CO2 gas is 31.6Nm 3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry blocks.
[0172] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0173] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0174] Performance Testing
[0175] The compressive strength of the carbon-solidified magnesium slag block prepared in the embodiment of the present invention after carbonization curing for 12 hours is 54.2 MPa, and the flexural strength is 6.0 MPa, as shown in Table 11.
[0176] Table 11 Mechanical properties after carbonization curing for 12 hours (MPa)
[0177]
[0178] Embodiment 11
[0179] The embodiment of the present invention provides a method for preparing a carbon-solidified magnesium slag building block, comprising the following steps:
[0180] Step 1: Mix water and Pidgeon magnesium slag evenly at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0181] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0182] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 24 hours. The volume concentration of the CO2 industrial tail gas is 60%, and the flow rate of the CO2 gas is 31.6Nm 3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry blocks.
[0183] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0184] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0185] Performance Testing
[0186] The compressive strength of the carbon-solidified magnesium slag block prepared in the embodiment of the present invention after carbonization curing for 24 hours is 60 MPa, and the flexural strength is 6.1 MPa, as shown in Table 12.
[0187] Table 12 Mechanical properties after carbonization curing for 24 hours (MPa)
[0188]
[0189] Example 12
[0190] The embodiment of the present invention provides a method for preparing a carbon-solidified magnesium slag building block, comprising the following steps:
[0191] Step 1: Mix water and Pidgeon magnesium slag evenly at a water-cement ratio of 0.4, and then cast to obtain magnesium slag blocks;
[0192] Step 2: Place the magnesium slag block obtained in step 1 at 20±1°C and relative humidity ≧90% for 24 hours, and then demould to obtain an uncarbonized magnesium slag block;
[0193] Step 3: Place the magnesium slag block obtained in step 2 in the mineralization box of the carbon capture device and introduce CO2 gas for mineralization maintenance for 72 hours. The volume concentration of the CO2 industrial tail gas is 60%, and the flow rate of the CO2 gas is 31.6Nm 3 / H magnesium slag slurry to obtain carbon-solidified magnesium slag slurry blocks.
[0194] Mineral composition analysis: XRD full spectrum fitting quantitative analysis technology was used to determine that the mineral components after grinding were mainly composed of β-C2S, γ-C2S and a small amount of calcium hydroxide, magnesium hydroxide and magnesium oxide.
[0195] The carbon-solidified magnesium slag building block prepared by the method for preparing a carbon-solidified magnesium slag building block in the embodiment of the present invention includes the following minerals in percentage by mass: C2S: 67%, CaCO3: 17%.
[0196] Performance Testing
[0197] The compressive strength of the carbon-solidified magnesium slag block prepared in the embodiment of the present invention after carbonization curing for 72 hours is 61 MPa, and the flexural strength is 6.2 MPa, as shown in Table 13.
[0198] Table 13 Mechanical properties after carbonization curing for 72 hours (MPa)
[0199]
[0200] Comparative Example 1
[0201] In the preparation method of magnesium slag blocks provided in this comparative example, in step 3, the prepared magnesium slag blocks are placed in a water bath for traditional hydration curing for 6 hours. Other methods and steps are the same as those in Example 1 and will not be repeated here.
[0202] The magnesium slag blocks prepared in the control example were subjected to mineral composition analysis and compressive strength test, wherein the mineral composition analysis method and the compressive strength test standard and method are the same as those in Example 1 and will not be described in detail herein.
[0203] In this control example, the compressive strength of the magnesium slag block after hydration curing for 6 hours is 28.4MPa, and the flexural strength is 2.4MPa.
[0204] The strength of magnesium slag blocks cured by traditional hydration is mainly due to the hydration reaction of the cementitious material components, which makes the interior become dense. However, due to the small proportion of cementitious material components and the poor pore structure inside the magnesium slag slurry under the traditional hydration curing method, the volume expansion will occur later, so the strength development is not ideal.
[0205] Comparative Example 2
[0206] In the preparation method of magnesium slag blocks provided in this comparative example, in step 3, the prepared magnesium slag blocks are placed in a water bath for traditional hydration curing for 12 hours. Other methods and steps are the same as those in Example 1 and will not be repeated here.
[0207] The magnesium slag blocks prepared in the control example were subjected to mineral composition analysis and compressive strength test, wherein the mineral composition analysis method and the compressive strength test standard and method are the same as those in Example 1 and will not be described in detail herein.
[0208] In this control example, the compressive strength of the magnesium slag block after hydration curing for 12 hours is 32.6MPa, and the flexural strength is 3.2MPa.
[0209] The extension of hydration curing time further deepens the hydration reaction of the cementitious material components, thereby increasing the content of hydration products and gradually improving the strength of the blocks.
[0210] Comparative Example 3
[0211] In the preparation method of magnesium slag blocks provided in this comparative example, in step 3, the prepared magnesium slag blocks are placed in a water bath for traditional hydration curing for 24 hours. Other methods and steps are the same as those in Example 1 and will not be repeated here.
[0212] The magnesium slag blocks prepared in the control example were subjected to mineral composition analysis and compressive strength test, wherein the mineral composition analysis method and the compressive strength test standard and method are the same as those in Example 1 and will not be described in detail herein.
[0213] In this control example, the compressive strength of the magnesium slag block after hydration curing for 24 hours is 36.8MPa, and the flexural strength is 3.6MPa.
[0214] Comparative Example 4
[0215] In the preparation method of magnesium slag blocks provided in this comparative example, in step 3, the prepared water magnesium slag blocks are placed in a water bath for traditional hydration curing for 72 hours. Other methods and steps are the same as those in Example 1 and will not be repeated here.
[0216] The magnesium slag blocks prepared in the control example were subjected to mineral composition analysis and compressive strength test, wherein the mineral composition analysis method and the compressive strength test standard and method are the same as those in Example 1 and will not be described in detail herein.
[0217] In this control example, the compressive strength of the magnesium slag block after hydration curing for 72 hours is 37.2MPa, and the flexural strength is 2.9MPa.
[0218] The present invention establishes a deep mineralization control mechanism, constructs a multi-factor synergistic performance optimization model, realizes the prediction of cement-based material mineralization performance and greatly reduces the emission of CO2 gas; develops a complete set of technology and integrated equipment for CO2 carbonization curing cement-based products. The carbon-cured magnesium slag blocks finally prepared reach a high strength in the early stage through short-term CO2 curing, and the unreacted C2S minerals continue to hydrate in the later stage to provide the later strength of cement.
[0219] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention shall be within the scope of protection of the pending claims of the present invention.
[0220] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and alterations may be made to the embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing all-solid waste cement products by mineralizing cement kiln tail gas, characterized in that: The following steps are involved: Step 1: Preparation of magnesium slag: Collect magnesium slag produced during magnesium smelting by industrial Pijiang method / silicothermic reduction method, and grind it into fine powder; Step 2, preparation of magnesium slag slurry: uniformly mixing the dried magnesium slag powder and water according to the target water-cement ratio to obtain a freshly mixed magnesium slag slurry; Step 3: Forming: pouring the magnesium slag slurry into a mold, forming it by oscillation, and demoulding it after preliminary solidification to obtain a magnesium slag block; Step 4: Mineralization treatment: Place the demoulded magnesium slag blocks in the mineralization box of the carbon capture device, inject CO2 gas into the mineralization box, and its volume concentration should be ≥30%; CO2 gas is introduced or purged through the inside or surface of the magnesium slag blocks to achieve mineralization; Step 5: Mineralization condition control: control the temperature of mineralization treatment to ≥ 0°C and the duration of mineralization treatment to ≥ 60 minutes; Step 6. Static curing: Before demoulding the prepared magnesium slag blocks, place them in a standard curing room for 24 hours.
2. The method for preparing all-solid waste cement products by mineralizing cement kiln tail gas according to claim 1, characterized in that: In the step 2, the mixing water accounts for 0.2-0.4 wt % and the Pidgeon magnesium slag accounts for 100 wt %.
3. A method for preparing all-solid waste cement products by mineralizing cement kiln tail gas according to claim 1 or 2, characterized in that: The volume concentration of CO2 gas in step 4 is ≥40%.
4. The method for preparing all-solid waste cement products by mineralizing cement kiln tail gas according to claim 3, characterized in that: The mineralization treatment is adjusted according to the carbon mineralization demand of the magnesium slag building block, and the duration of the mineralization treatment is ≥120 minutes.
5. The method for preparing all-solid waste cement products by mineralizing cement kiln tail gas according to claim 1, characterized in that: The mold volume in step 3 is 40*40*160mm 3 .
6. The method for preparing all-solid waste cement products by mineralizing cement kiln tail gas according to claim 5, characterized in that: The content of silicon dioxide SiO2 in the Pidgeon process magnesium slag is 29.88wt%; the content of aluminum oxide Al2O3 in the Pidgeon process magnesium slag is 1.06wt%; the content of CaO in the Pidgeon process magnesium slag is 50.98wt%.
7. The method for preparing all-solid waste cement products by mineralizing cement kiln tail gas according to claim 3, characterized in that: The CO2 gas captured by cooling is waste gas containing CO2 generated during fuel combustion and production process in cement plants.
8. The method for preparing all-solid waste cement products by mineralizing cement kiln tail gas according to claim 1, characterized in that: The Pijiang magnesium slag in step 1 includes the following components: silicon dioxide SiO2, aluminum oxide Al2O3, calcium oxide CaO, iron oxide Fe2O 3 , magnesium oxide MgO.
9. The method for preparing all-solid waste cement products by mineralizing cement kiln tail gas according to claim 1, characterized in that: The fineness of the Pidgeon magnesium slag in the step 1 is less than 75 μm.
10. The method for preparing all-solid waste cement products by mineralizing cement kiln tail gas according to claim 1, characterized in that: The temperature for casting the magnesium slag blocks is 19-21°C.